Consumption patterns of livestock products in Ethiopia: Elasticity estimates using HICES (2004/05) data - Worku, Ibrahim; Tafere, Kibrom (International Food Policy Research Institute, 2012)
This study examines the consumption patterns of livestock products in Ethiopia. The contribution of livestock products to households’ daily consumption is very limited. A considerable difference exists between urban and rural areas and the consumption of livestock products rises significantly with income. We found substantial expenditure and price responses for livestock products with higher price responses in rural areas than urban areas. A strong substitution relationship among most livestock products exists, the only exception being dairy products. The results seem to indicate the existence of constraints imposed on the consumption choices for livestock products in Ethiopia.